An experimental investigation of liquid cooling scheduling for a battery module. (13th January 2020) - Chen, Siqi; Bao, Nengsheng; Gao, Liang; Peng, Xiongbin; Garg, Akhil
Summary: The thermal safety of electric vehicle battery modules attracts public concern; controlling the severe temperature rise and ensuring uniform temperature distribution are essential to addressing this problem. In this research, a liquid cooling‐based cooling structure equipped with minichannels is proposed to prevent a battery module's overheating. A novel cooling scheduling study is proposed to arrange the coolant flow rates at different cooling stages. The temperature rise, temperature difference, and energy consumption of all the cooling schedules are measured in experiments. Experimental findings indicate that appropriate cooling scheduling achieves the thermal objectives and reduces energy consumption through scheduling the coolant flow rate in the cooling process. A comprehensive cooling schedule selection is carried out to select the optimal cooling schedule with the highest cooling efficiency through evaluating both the thermal and energy consumption objective parameters under different discharging current rates (0.5C, 1C, and 1.5C). The optimal cooling schedule maintains the maximum temperature of the battery module within 26°C, 32°C, and 40°C under 0.5C, 1C, and 1.5C discharging current rates, respectively. Moreover, the temperature SD and the energy consumption of the liquid cooling‐based battery pack can be controlled within 3.5°C and 40 J, respectively. Abstract : A novel liquid cooling‐based scheduling method is developed for a battery module. The temperature distribution and energy consumption of the cooling process are studied. The optimal liquid cooling schedule is selected considering the battery module's thermal performance under different current rates.